Ethyl cyanoacetate - a versatile reagent - Mrunali, Kale S. (Research Journal of Chemistry and Environment, 2008)
Ethyl cyanoacetate is widely used as an active methylene reagent in variety of condensation reactions. It also plays a very important role in organic synthesis as well as in medicinal chemistry due to ease formation of C-C bond formations reactions.